2005
DOI: 10.1111/j.1475-4959.2005.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of vulnerability: locating coping strategies in Kenya and Tanzania

Abstract: We investigate how smallholder farmers at two sites in Kenya and Tanzania cope with climate stress and how constraints and opportunities shape variations in coping strategies between households and over time during a drought. On the basis of this analysis, we draw out implications for adaptation and adaptive policy. We find that households where an individual was able to specialize in one favoured activity, such as employment or charcoal burning, in the context of overall diversification by the household, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
211
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(224 citation statements)
references
References 48 publications
(44 reference statements)
12
211
0
1
Order By: Relevance
“…Socio-economic factors clearly drive choice of coping activity. Indeed our findings resonate for example, with those of Eriksen et al (2005) that gender is important in household decisions to specialise in an activity.…”
Section: Diversification Driverssupporting
confidence: 81%
See 2 more Smart Citations
“…Socio-economic factors clearly drive choice of coping activity. Indeed our findings resonate for example, with those of Eriksen et al (2005) that gender is important in household decisions to specialise in an activity.…”
Section: Diversification Driverssupporting
confidence: 81%
“…However, non-farm income generating activities may not be reliable during droughts as the overall income and therefore spending within a community dependent on natural resources may decrease (Eriksen et al 2005). Nonetheless, some studies observed such activities increase during drought (Cunguara et al 2011) especially in market-orientated communities where there is more continuous trading activity.…”
Section: Resources Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Local knowledge in disaster risk management is critical for reducing vulnerability among the poorest, and can be combined with policy efforts to address social equity and vulnerability. Any policy intervention to strengthen adaptation and reduce risk would need to recognize community participation in disaster prevention and response and strategies for living with environmental variability (Wisner et al, 2004;Eriksen et al, 2005;Pelling and High, 2005;van Aalst et al, 2008).…”
Section: Key Principle 3: Integrate Local Knowledge Into Adaptation Rmentioning
confidence: 99%
“…In Mexico, future planning was unfamiliar to the community as their primary focus was on the routine of 'daily activities' rather than long-term issues, indicative of a reliance on coping mechanisms (Eriksen et al, 2005). However, during the process participants expressed satisfaction at 'having been given the opportunity to think about the future'.…”
Section: Scenario Developmentmentioning
confidence: 99%